PENGARUH HARGA, KUALITAS PRODUK, DAN LOKASI TERHADAP MINAT BELI KONSUMEN DALAM MEMBELI BERAS - Rahayu, Rahayu Lesninghati; Souisa, Johanis; Utomo, Afi Zuhriyah; Wardani, Savira Kusuma; Ardani, Vardila (Sekolah Tinggi Ilmu Ekonomi SBI, 2023)
This research aims to examine the influence of price, product quality and location on interest in buying local rice at UD Rahayu in Blora. This research was conducted using a survey method of consumers who had made purchases at UD Rahayu and the sampling technique used was purposive sampling, totaling 96 respondents. Data collection was through distributing questionnaires, data analysis in this study used SPSS 26. The analysis used in this research included Validity Test, Normality Test, Classical Assumption Test, Multiple Linear Regression Analysis Test and Research Hypothesis Test. The research results show that price, product quality and location have a positive and significant effect on consumers' buying interest in buying local rice at UD Rahayu in Blora. Based on the Coefficient of Determination (R²) value of 54%, consumer buying interest variables can be influenced by price, product quality and location.Keywords: price; product quality ; location; interest in buying